Knowledge of Prenatal Care Nurses toward Management of Toxoplasmosis in Pregnant Women - Khudair, fatima (Iraqi National Journal of Nursing Specialties, 2013)
Objective: This study aims to assess the level of nurse’s knowledge regarding toxoplasmosis management in pregnant women. Methodology: A descriptive analytic study was carried out from January 2012 to March 2012. A sample of (70)nurses who provide prenatal care to pregnant women at primary health care centers of AL-Adala,ALHindia,AL-Askary,AL-Jamea,AL-Ansar and AL-Salam in AL-Najaf city. The questionnaire was self-completed and included questions on sociodemographic characteristics and toxoplasmosis aspects. Results: The findings of the study indicated that (44.3%) of nurses have moderate level of knowledge. (32.9%) of nurses was with age ranging from 31-36 years. (74.3%) were male. (52.9%) were secondary graduate,(31.4) were institute graduates, regarding the training sessions the majority of nurses (84.3%)have no training sessions, (34.3%) of nurses who were included in the study have duration of experience ranging from 7-13 years. Highly significant relation between nurse‘s level of knowledge and their age and years of experience (0.009, 0.024) respectively Recommendations: The study recommended that: it is necessary to join all nurses who work in prenatal care units in workshop training, continuing education sessions regarding toxoplasmosis aspects and other mother –child issues to improve health awareness. Another study should be conducted to investigate the association between the prevalence of toxoplasmosis and affectivity of prenatal care in preventing toxoplasmosis.